POTENSI DEPOSIT WOLFRAM DI INDONESIA: STUDI KASUS TOBOALI - BANGKA SELATAN - Imelda Eva Roturena Hutabarat; Sabtanto Suprapto; Priatna Priatna; Maryono Maryono; Rudiyansah Rudiyansah (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Bangka island is one of the islands in the Southeast Asian Tin Belt that makes Indonesia the largest tin (Sn) producer in the world. The carrier of wolframite is a by product mineral of the mineral tin (cassiterite). This study aims to study the presence and type of wolfram-as by product in the tin deposits on Bangka island. The research area was conducted on the eastern edge of Klabat Granite in Kepoh Village, Toboali District, South Bangka, at coordinates of 106o 31' 58